(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the influence of the role playing learning model combined with audio-visual media on students’ learning interests. The role playing model provides opportunities for students to actively participate by acting out certain situations that are relevant to the learning material, while audio-visual media is used to strengthen students’ understanding through visualization and interesting narratives. The combination of the two is designed to create an interactive and fun learning atmosphere, so that it can increase students’ motivation to learn. The research method uses a literature study approach by analyzing 20 scientific articles published during the 2020–2024 period. The data was collected through platforms such as Google Scholar and ResearchGate using the keywords "Role Playing," "Audio Visual Media," and "Learning Interest in IPAS.". The data were analyzed in a qualitative descriptive manner, focusing on the main findings of each article. The results of the study show that the use of the role playing model with audio-visual media significantly increases students’ interest in learning. Students become more enthusiastic, actively involved in learning, and show a better understanding of the subject matter. The results of the study also revealed that the application of this model is not only effective in increasing learning interest, but also has the potential to develop students’ critical thinking, communication, and collaboration skills